Increase in dental caries and change in the socioeconomic profile of families in a child cohort of the primary health care in Northeast Brazil - Márcia Maria Dantas Cabral de Melo; Wayner Vieira de Souza; Paulo Sávio Angeiras de Goes (BMC Oral Health, 2019)
Abstract Background Factors associated with increases in dental caries and changes in the family socioeconomic profile were investigated in a paediatric primary health care (PHC) cohort in Northeast Brazil during the implementation of social and income transfer programmes. Method A prospective analytical study compared data from two surveys on caries in primary dentition conducted in 2006 (age: 18–36 months, n = 1045) and 2010 (age: 5–7 years). Data from the sample recruited and re-examined in 2010 (n = 469) were analysed. Prevalences (P) and the mean primary decayed, missing and filled teeth (dmft) index, cumulative incidence and mean increase were calculated. Differences (p ≤ 0.05 and 95% CI) in dmft ≥1 were identified via McNemar’s test. Differences in the mean dmft were evaluated according to socioeconomic variables (Kruskal-Wallis test and p ≤ 0.05). Multivariate analysis with a negative binomial model was used for the risk factors associated with increasing dmft. In the univariate analyses, nonparametric methods (Kruskal-Wallis test) were used to compare subsamples. Variables with p ≤ 0.20 were included in the multivariate model and retained when p ≤ 0.05. Results The prevalence and mean dmft (18–36 months and 5–7 years: p = 28.6 and 68.9%, mean = 1.01 and 3.46, respectively) and variation in mean dmft changed significantly (p < 0.005) with the education level and occupation of the mother; the prevalence and mean dmft were lower for higher maternal education level and maternal participation in the labour market. The cumulative incidence and mean increase in dmft were 8.71% and 2.45, respectively. Common risk predictors for increases in caries were consumption of sweets (RR = 1.53, 95% CI 1.09–2.14) and attendance at public schools (RR = 1.49, 95% CI: 1.81–1.89). Use of private clinical services was a protective factor (RR = 0.68, 95% CI 0.54–0.87). Conclusion Increases in caries were observed despite positive changes in the distribution of socioeconomic indicators for the analysed children’s families. The risk factors identified for the increase in caries suggest ongoing problems regarding the effectiveness of intersectoral and health measures for controlling caries in populations exposed to PHC programmes.